Occluded cobalt species over ZSM-5 matrix: Design, preparation, characterization and magnetic behavior - Pierella, Liliana Beatriz (2007)
Co-containing molecular sieves with MFI structure was synthesized by the hydrothermal crystallization method and cobalt was incorporated in it by wet impregnation at different percentages. Thermal post-treatments were applied to Co-ZSM-5: calcination and reduction. X ray diffraction (XRD) and FTIR studies confirmed crystallinity, structure and orthorhombic symmetry of the obtained samples (Co-ZSM-5 calcined and Co-ZSM-5 reduced). The XRD, Raman spectroscopy, SEM and TPR techniques for the calcined samples showed the presence of Co3O4 which diminished in the reduced samples and Co0 appeared. The magnetic behavior of the materials was evaluated by magnetization (M) variation with applied magnetic field (H) at different temperatures. Low magnetization is observed in the calcined samples while high values are ttained in the reduced samples, due to the presence of metallic Co.